Impact of Personality on Choice of Instructional Delivery and Students' Performance. Issue 3 (2nd July 2020) - Chesser, Svetlana; Murrah, William; Forbes, Sean Alan
ABSTRACT: This study was designed to investigate how college students' personality characteristics relate to their choice of instructional delivery (online or face-to-face) and whether this choice mediates the relationship between personality and academic performance. One hundred eighty-eight undergraduate students were given a choice between taking the same general education course online or face-to-face. Students completed the Big Five Inventory (BFI) upon the conclusion of this course. Using a Bayesian regression course modeling framework, we found that Conscientiousness and Agreeableness were related to the choice of instructional delivery. Students scoring higher on Conscientiousness and lower on Agreeableness tended to choose the online environment. Conscientiousness also was a direct predictor of academic achievement regardless of the course environment. These results suggest that in order to find the best fit between student and the learning environment, it is important to identify personality characteristics indicative of success in online and traditional face-to-face courses to help students to become more efficient learners and assist faculty in designing quality courses to meet students' needs.